Obesity Hypoventilation Syndrome - Harles Sitompul; Aura Ihsaniar (Journal of Anesthesiology and Clinical Research, 2022)
Obesity Hypoventilation Syndrome or commonly abbreviated as OHS, is a respiratory disorder that often occurs in patients characterized by decreased oxygen levels and increased carbon dioxide in the blood. Based on the criteria of the World Health Organization (WHO), the definition of obesity is if the BMI is equal to or greater than 30 kg/m2. The classification of obesity is BMI 30-34.9 kg/m2, 35-39.9 kg/m2 and > 40 kg/m2. The pathophysiology of OHS is still not fully known with certainty. Severe obesity causes an increase in the burden on the respiratory system, weakness of the respiratory muscles, leptin resistance, and respiratory disturbances during sleep, causing a decrease in the sensitivity of the ventilation center response, which can lead to hypoventilation and hypercapnia. Basically, there are six points of OHS management, including a weight loss program, oxygen therapy, positive pressure ventilation, pharmacotherapy, tracheostomy, and management of OHS complications.